Kompetensi Absolut dan Aktivisme Yudisial dalam Peran Mahkamah Agung Menguji Anggaran Dasar Partai Politik di Indonesia - Kurniawan, Denis (UI Scholars Hub, 2024)
This article examines the necessity for the Supreme Court to extend its absolute competence in conducting judicial reviews (right to judicial review) of the Articles of Association and/or Bylaws of Political Parties, which serve as the object of review (objectum litis). This article was prepared by doctrinal research methods. Political parties are institutions that are known for their existence, authority, and constitutional dissolution through the 1945 Constitution. As such, the Articles of Association and Bylaws of Political Parties can be defined as regulations that are established by a Political Party based on orders from higher legal norms, namely the law. It is imperative that the content and procedures for the formation of political parties do not conflict with the legal norms. Accordingly, in the event of a discrepancy between the Articles of Association and/or Bylaws of a Political Party and higher statutory regulations, the Supreme Court, as a judicial control institution, is responsible for determining the validity of the legal norm. The request for a review of amendments to the 2020 Democratic Party's Articles of Association and/or Bylaws, as presented in case Number 39 P/HUM/2021, was not addressed by the Supreme Court in a comprehensive manner. A review should have been conducted in a gradual manner, through the implementation of legal innovations (i.e., rule-breaking measures) aimed at safeguarding the constitutional rights of citizens, which have been disregarded and violated by the enactment of a political party's articles of association and/or bylaws.